Early Clinical Experience with Bleomycin in the United Kingdom in Series of 105 Patients - Halnan, K. E. (1972)
The results of treating a series of 105 patients (79 with advanced squamous cell carcinoma, 21 with advanced lymphoma, and 5 with miscellaneous tumours) with bleomycin are described. The drug was usually given as a single agent. Four patients with squamous cell carcinoma showed complete regression and there was partial regression in 25. Side effects were frequent, particularly skin changes and stomatitis; death from pneumonitis occurred in one patient.